2009
DOI: 10.1017/s0014479709990548
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Physiological Effects of System of Rice Intensification (Sri) Practices Compared With Recommended Rice Cultivation Practices in India

Abstract: SUMMARYAn evaluation was conducted in eastern India over three years, 2005–2007, to compare the performance of certain System of Rice Intensification (SRI) practices: transplanting single, young (10-day-old) seedlings in a square pattern; no continuous flooding; and use of a mechanical weeder – with those currently endorsed by the Central Rice Research Institute of India, referred to here as recommended management practices (RMP). All plots received the same fertilization, a combination of organic and inorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
86
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(114 citation statements)
references
References 37 publications
11
86
0
1
Order By: Relevance
“…Normally, HI of highyield varieties grown in irrigated fields range between 0.4 and 0.5 (Chang and Li 1991). Therefore, the HIs of Zhao et al (2009) and Thakur et al (2010b) obtained in conventionally flooded practices were a little bit lower than the normal value. There is no consistent result for biomass production and HI compared between SRI and conventional practices.…”
Section: N Uptake and Biomass Production Or Grain Yieldmentioning
confidence: 90%
See 4 more Smart Citations
“…Normally, HI of highyield varieties grown in irrigated fields range between 0.4 and 0.5 (Chang and Li 1991). Therefore, the HIs of Zhao et al (2009) and Thakur et al (2010b) obtained in conventionally flooded practices were a little bit lower than the normal value. There is no consistent result for biomass production and HI compared between SRI and conventional practices.…”
Section: N Uptake and Biomass Production Or Grain Yieldmentioning
confidence: 90%
“…The harvest index (HI) of rice plants under SRI (0.44-0.51) was higher than under traditional flooding (0.38-0.45) (Zhao et al 2009). Thakur et al (2010b) reported that biomass production of SRI was the same as that with RMP, but the grain yield of SRI was significantly higher than RMP. This difference was attributed to the difference in HI.…”
Section: N Uptake and Biomass Production Or Grain Yieldmentioning
confidence: 90%
See 3 more Smart Citations